Approaches to Defining a Television Format as one of Intellectual Property Law objects: Ukrainian and Foreign Experiences - Sylkina, Alena (European Journal of Sustainable Development, 2020)
In this article the author analyzes theoretical approaches which were formulated due to the appearance of complex objects of Intellectual Property Law. The attention is concentrated on the analysis of concepts that investigate the legal nature of a television format. The author considers that it is necessary to differentiate a positive approach which recognizes that a format is an object of Intellectual Property Law and negative approach which denies the possibility of television formats protection. Through the method of comparison between the scientific doctrine and judicial practice in the countries of the Romano-Germanic and Anglo-Saxon legal systems, the author classifies concepts to be developed by theoretic community. Thus, negative approach of the Romano-Germanic Legal system countries is confirmed by normative legal acts which relate to the ideas, methods and concepts. Representatives of the Anglo-Saxon Legal system make it impossible to protect a format within the doctrines: "scene a fair", "idea\expression", "merger", etc. The author prefers the positive approach which is divided into the following concepts of the analysis of a format: as a dramatic work (according to Copyright Law), as a hybrid object, as a synthetic object, as a compilation, as a complex object of IP Law. The author gives the definition to a television format, explains its legal nature, and views a format as one related to the concept of complex Intellectual Property Law objects. She analyzes judicial practice which has developed in Ukraine and abroad. Taking into consideration the fact that relations which are connected with the distribution of a format have not only national, but also global character, it is important to unify the given approaches and to use them in legislature. It is relevant to enhance and standardize the legislation in the television field which would contribute to the development of contractual relations between the countries. Keywords: tv-format, television format, complex object, hybrid object, intellectual property